Produtividade das indústrias de cera de carnaúba no estado do Piauí - Araújo, José João Siqueira de (2008)
The general objective of this study is to analyze the productivity of five (5) wax industries of carnaúba in the state of Piauí, that corresponds to 41,6% of the total of industries of the state. The industries had been considered for ends of analyses of: small, average and great transport, aiming to contribute for the increment of this segment. The variable key was the productivity, proceeding from the process of monthly production of the wax of carnaúba in tons and the number of employees used in a month. The study shows the relation between productivity, real wage, consumption of firewood and dollar exchange. Allowing to raise the hypothesis of that the productivity is influenced by these three variables. The data was obtained by means of two instruments, a spread sheet, elaborated for this research, enclosing the period of 2003 2006, forty and eight months, totalizing two hundred and forty comments and an interview with the five proprietors. The analysis of the data was carried through three moments: at the first moment it was done a descriptive analysis of the five industries, its localization, number of employees and, the importance for the economy of the region. At the second moment, it was done a financial analysis of the researched wax industries of carnaúba, perceiving its profitability and liquidity and, the third elaborated analysis, to verify the productivity was by means of econometrical modeling. The second analysis prepared for evaluating the productivity was estimated an econometric model with panel data. And for this, was used in the production function of the type Trans-log, which was estimated, this model was estimated by Random effect and used the method of Generalized Least Squares and, in relation to the results, it can be inferred that the productivity of industries of carnaúba wax, are positively influenced by spent on firewood and negatively with the spent on electricity. In addition, this sector is intensive in the use of firewood and can be explained by the low cost of this input.